Difference Equation for $N$-Body Type Problem (Communications in Mathematical Research, 2021)
In this paper, the difference equation for $N$-body type problem is established, which can be used to find the generalized solutions by computing the criticalpoints numerically. And its validity is testified by an example from Newtonian Three-body problem with unequal masses.
Keywords: Difference equation; $N$-body type problem; critical point.